Varietal differences in proximate composition of selected commonly consumed vegetables of Bangladesh (Bangladesh Journal of Nutrition, 2018)
Vegetables are considered as protective food due to their diverse nutrient content and wide range of health benefits they exert. Being plant origin, nutrient composition of vegetables depends on botanic and cultivar’s origin, geographical area, climate and others. Present study was carried out to estimate the proximate composition of 17 varieties of commonly consumed vegetables: Sweet Pumpkin, Radish, Tomato, Brinjal and Bottle gourd. All samples were collected from the research field of Bangladesh Agricultural Research Institute (BARI), which is involved in development of new varieties through a standard cultivation system. The moisture, protein, fat, TDF, ash and carbohydrate content were estimated. The moisture content in selected samples ranges from 86.86% (Brinjal; Begun-3)to 96.74% (Radish: Mula-3), protein from 0.45% (Tomato-14) to 1.73 (Brinjal: Begim-10, Begun-6), fat from 0.02%(Radish: Mula-2) to 0.62% (Brinjal: Begun-3), ash from 0.39% (Sweet pumpkin; Mishtikumra-1) to 8.14%(Tomato-14), TDF from 0.22% (Bottle gourd: Lau-2) to 4.31% (Brinjal; Begun-Uttara), available carbohydrate from0.75% (Brinjal: Begim-3) to 7.67% (Radish; Mula-3) and energy from 9.98 Kcal/lOOg (Brinjal- Begun-3) to 46.26 Kcal(Radish: Mula-3). The differences in nutrient content among different varieties varied from around 4-37% for Sweet pumpkin, 3-44% for Radish, 2-74% for Tomato, 8-94% for Brinjal and 17-51% for Bottle gourd. The present findings indicate that nutrient composition differs to a large extent due to the variation in varieties which in fact allows people to choose desired variety while planning diet and also allows to link nutrition and agriculture sectors for better nutritional status of the population. However, further research work should be carried out on other nutrient content of such different species to reveal the complete nutritional profile in terms of variation.Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 33-38